The Effectiveness of Using SISKOHAT (Integrated Hajj Information and Computerization System) in the Hajj Pilgrim Candidates’ Portion Number Delegation Service at the Ministry of Religious Affairs in Bengkulu Province - Angraini, Syafitri; Hak, Nurul; Makmur, Makmur (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2022)
This study aims to determine the effectiveness of using SISKOHAT (Integrated Hajj Informationand Computerized System) in the hajj pilgrim candidates’ portion number delegation service. Tofind out the obstacles faced in SISKOHAT, portion delegation, and evaluate the service systemprovided by the umrah and hajj organizer, registration and hajj documents section, to Hajjpilgrims candidates. SISKOHAT is a work support tool in organizing the pilgrimage by utilizinginformation technology in Indonesia and Saudi Arabia. The results of this study indicated thatSISKOHAT at the Head of Hajj Registration and Documents for the Implementation of HajjUmrah at the Regional Office of the Ministry of Religion Province Bengkulu had been effective inthe service of delegating portion numbers to pilgrim candidates.